Certain young women confronting their destiny: A Reconsideration of Middle-march, The Rainbow and Women in Love in the light of recent feminist criticism - Abbotts, Elisabeth Sheena (My University, 1979)
Concurrent with the resurgence of interest in feminism over the past twenty years has been a reconsideration of the portrayal of women in literature and an attempt to define a self-consciously feminist aesthetic. The first chapter of this thesis attempts to provide an over-view of the theoretical questions being raised by feminists about literature. The three subsequent chapters re-examine the search for self-identity in George Eliot's Middlemarch and D.H. Lawrence's The Rainbow and Women in Love in the light of feminist critiques of the novels.
[missing page 130]
Keywords: English; English Language and Literature; English Language and Literature